Research on the Transformation of Errenzhuan from the Perspective of Short Videos - Li, Zhenyao (Pacific International Journal, 2025)
This study examines the transformation of Errenzhuan, a traditional Northeast Chinese folk art, through the lens of short video platforms. Confronting a shifting cultural landscape, Errenzhuan’s migration to digital media represents a critical case of "creative transformation" for intangible cultural heritage. The research analyzes how platforms like Douyin reconfigure its artistic form, cultural meaning, and communication logic, revealing a dualistic impact. While short videos demolish geographical and generational barriers, creating a participatory ecosystem where users evolve from audience to co-creators through secondary creations and challenges, this adaptation also poses significant risks. The fragmentation of narratives, exaggeration for algorithmic appeal, and dominance of traffic logic often lead to entertainment overload and a dilution of artistic essence. The study concludes that authentic revitalization hinges on upholding integrity while innovating—using the art’s core aesthetic values as an anchor to harness, rather than be subsumed by, platform dynamics. Thus, Errenzhuan’s journey illustrates a precarious yet promising path for folk arts navigating the digital age, balancing technological empowerment with cultural preservation to achieve sustainable relevance.